2006
DOI: 10.3200/jach.55.1.41-46
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Body Weight and Fat Mass of Men and Women in the First Year of College: A Study of the "Freshman 15"

Abstract: Students entering their first year of college are faced with many stresses and changes, including changes in eating and exercise behavior. A common but often undocumented myth among college students is that there is a high risk of gaining 15 pounds of weight during freshman year. The objective of this study was to measure changes in body weight and percentage of body fat among first-year college students. Using a digital scale with bio-electrical impedance, the authors measured height, weight, and percentage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
137
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(147 citation statements)
references
References 2 publications
9
137
1
Order By: Relevance
“…This is why creating a proper model of teaching about nutrition and healhy behavior at the universities we studied is an important goal of our work. It is crucial to point out that the student lifestyle, especially in the first years at university, is often unhealthy [21].…”
Section: Discussionmentioning
confidence: 99%
“…This is why creating a proper model of teaching about nutrition and healhy behavior at the universities we studied is an important goal of our work. It is crucial to point out that the student lifestyle, especially in the first years at university, is often unhealthy [21].…”
Section: Discussionmentioning
confidence: 99%
“…While the so-called "Freshman 15" is more likely to be the "Freshman 5" (Megel et al, 1994, Matvienko et al, 2001, Anderson et al, 2003, Butler et al, 2004, Levitsky et al, 2004, Levitsky et al, 2006, Hajhosseini et al, 2006, Hoffman et al, 2006, Morrow et al, 2006, Holm-Denoma et al, 2008and LloydRichardson et al, 2009, college freshmen gain weight at a greater rate than do others in the general population (Levitsky et al, 2004). Furthermore, larger prospective studies show that weight gain as a young adult tends to set the pace for weight gain well into adulthood (Truesdale et al, 2006 andLloydRichardson et al, 2009).…”
Section: Weight Gain and Obesity In Young Adultsmentioning
confidence: 99%
“…This paper reported the results of three trials conducted in the US and Europe, two of which were carried out for a year and the third for three years. The combined trials, which observed more than 2,300 women (aged [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35], reported modest weight gain (<2.3kg at 12 months) with large individual variation 53 .…”
Section: Activitymentioning
confidence: 99%
“…Nine papers were allocated to one of these categories. The remaining 20 papers focussed on university populations [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] .…”
Section: Stage Onementioning
confidence: 99%